Fracture network characterization of high-rank coal and its control mechanism on reservoir permeability - Liu, Yanhao; Xiong, Zuqiang; Zhang, Xiaodong (Frontiers in Earth Science, 2022)
Based on the results of previous research on the fracture systems of reservoirs of middle- and low-rank coal, we took high-rank coal in the southern Qinshui Basin as the study object in this paper and summarize the characteristics of both macro- and micro-fractures in reservoirs of different rank coals, establish a geometric model of the fracture network for different rank coals, and explore the mechanism of coal reservoir permeability change under different conditions. Based on the research, we found that the structure of the fracture network of high-rank coal developed unevenly. The high-rank coal had the characteristics of rift created outside, micro-fracture development, and undeveloped endogenous fracture, which can be used to improve the permeability of the coal reservoir, to a certain extent. We concluded that given the absence of a seepage aisle in the high-rank coal, there is a rapid increase in the permeability of the reservoir, with the fracture width increasing from the lower road to the higher road. However, the seepage rate in other coal rank reservoirs increases smoothly. Due to fracture compression and coal matrix shrinkage, the permeability of the coal reservoir first decreases and then increases during the drainage stage. At the same rate of pressure drop, the permeability of high-rank coal reservoir decreases at the fastest rate, followed by that of low-rank coal reservoir, and that of middle-rank coal reservoir, in that order.